2018
DOI: 10.1007/s00586-018-5593-1
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary cement embolism following cement-augmented fenestrated pedicle screw fixation in adult spinal deformity patients with severe osteoporosis (analysis of 2978 fenestrated screws)

Abstract: This study showed an overall 16.3% radiological PCE and 1.4% symptomatic PCE incidence when CAFPS were used due to severe osteoporosis. The symptomatic PCE risk was significant when CAFPS were > 7 levels; > 14 fenestrated screws; and > 20-25 cc cement volume is used and this may cause PAP increase and right ventricular dilatation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 22 publications
2
38
0
1
Order By: Relevance
“…Methods to reduce CL in LDD include: (1) Using high viscosity cement or toothpaste viscosity cement [28]. (2) Reducing the volume of cement and the number of augmented screws [29,30]. Experimental studies have indicated that the screw stability does not significantly improve when the volume of PMMA exceeded 2.8 ml each screw [25].…”
Section: Discussionmentioning
confidence: 99%
“…Methods to reduce CL in LDD include: (1) Using high viscosity cement or toothpaste viscosity cement [28]. (2) Reducing the volume of cement and the number of augmented screws [29,30]. Experimental studies have indicated that the screw stability does not significantly improve when the volume of PMMA exceeded 2.8 ml each screw [25].…”
Section: Discussionmentioning
confidence: 99%
“…(2) Reducing the volume of cement and the number of augmented screws. The large volume of bone cement and augmented screw resulting in increasing possibility of secondary venous wall rupture and cement pressed in [29,30]. Experimental studies also have indicated that the screw stability doesn't significantly improve with the volumes of PMMA above 2.8 ml each screw [25].…”
Section: Discussionmentioning
confidence: 99%
“…In surgical treatment of patients with osteoporosis, cement-augmented fenestrated pedicle screw (CAFPS) had been safely used 15,21 . CAFPS could provide comparable screw stability to solid pedicle screws augmented with high-viscosity cement 22 .…”
Section: Discussionmentioning
confidence: 99%
“…After con rmation of all screws position via AP and lateral uoroscopy, cement augmentation was performed via cement delivery cannulas. In all cases of group A, the same polymethylmethacrylate (PMMA) bone cement was applied in a standard fashion as described by previous report 15 . UIV and LIV of all patients were xed with CAFPS and other surgical segments were xed using conventional pedicle screws or CAFPS according to intraoperative assessment of poor bone quality.…”
Section: Surgical Protocol Of Group Amentioning
confidence: 99%